No small change : why financial services needs a new kind of marketing - Camp, Lucian, 1953- 4 0 16; 1954- Thomson, Anthony; 5 (Chichester, West Sussex, United Kingdom : John Wiley & Sons, 2018)
A 13-point manifesto for a new financial services marketing model Anthony Thomson knows a thing or two about new and disruptive financial services, having co-founded and chaired first the ground-breaking Metro Bank and then the purely digital, app-based Atom Bank.' And as a financial services marketing specialist for over 30 years, Lucian Camp has helped develop more new and innovative financial services propositions than anyone. Now they've put their heads together to write No Small Change, a passionate, opinionated and practical manifesto arguing that the fast-changing financial services world urgently needs to rethink the whole of its approach to marketing.' Most of all, they propose that an increasingly digital, fintech-driven industry needs not just more marketing, but also better marketing to make sure it's successfully identifying consumers' real needs, and finding powerful and successful ways to engage with them. After detailing the forces of change that demand a new approach, the book then examines in 13 chapters what the key components of that new approach should look like.' It takes a broad and multi-faceted perspective, exploring areas as diverse as the crisis of consumer trust, the ever-growing power of Big Data, the importance of leadership and corporate culture and the rapid advance in thinking based on Behavioural Economics. In developing these themes, the authors don't pull their punches.' The book is fiercely critical of some of the industry's long-established marketing habits, providing compelling reasons why it's time to abandon the practices that have given it a bad name.'' Marketers will applaud, but the book is also intended for a broader audience.' Thomson and Camp challenge senior management in financial firms to appreciate the real value that marketers can bring to shaping the business agenda at the highest level, and not just to label marketing with that tired old phrase 'the colouring-in department.' Rich in anecdotes, comments from leading industry figures, personal experiences on the part of both authors and findings from original research, No Small Change is an entertaining and rewarding read ' and, at this point in the development of financial services, a timely and important one.' '
Cover; Title Page; Copyright; Contents; Preface; Acknowledgments; About the Authors; Chapter 1 About This Book; Chapter 2 What Is Marketing, And Why Does It Matter?; Chapter 3 From 'Best Advice' to 'Satisficing'; Chapter 4 Why Not Then? And Why Now?; A Note On Selling vs Marketing; Chapter 5 Retail Financial Services How?; Annuities; Cards; Critical Illness Insurance; Current Accounts; Equity Release; Financial Advice; Funds; Gambling; INCOME REPLACEMENT INSURANCE (Misleadingly Named Permanent Health Insurance); Life Assurance; Lending; Mortgages; Motor Insurance; Payday Lending.;Peer-to-Peer LendingPensions (Accumulation); Pensions (Decumulation); Price Comparison Sites; Private Medical Insurance; Robo Advice; Savings; Travel Insurance; Travel Money (FX); Wealth Management; Chapter 6 Real People, Real Lives; Chapter 7 Cutting in the Middle Man; The Intermediary Market Today; The New Intermediary Marketing; Chapter 8 Introducing the New Financial Services Marketing; The New Financial Services Marketing; Chapter 9 How Does Your Firm Define Its Purpose?; Background Test 1: Has the stated purpose been adopted recently?;Background Test 2: Is the organisation large, complicated and siloed?Background Test 3: Similarly, as a customer, are you dealing with a peripheral part of a large, complex business?; Background Test 4: How is the business's relationship with its external shareholders?; Background Test 5: Is the business finding it easy to make money?; Chapter 10 Does Your Firm Have a Strong and Distinctive Culture?; Chapter 11 How Much Is Big Data Changing Your Business?; Chapter 12 Do You Get the Power of Behavioural Economics?; Chapter 13 Are You Really Any Good at Innovation?;Chapter 14 Are You Absolutely Sure About 'Restoring Trust'?Chapter 15 Whatever It Is, Can You Make It Simpler?; 'Attitude to Risk' Questionnaires; Chapter 16 Are You Just a Little Bit Boring?; Chapter 17 Call That a Brand?; Some Brand Myths Debunked; Brand Architecture and Product Branding; Chapter 18 Yes, But Can You Prove It's Working?; Chapter 19 Must Planning Your Comms Be So Horribly Complicated?; It's Broadcast and Narrowcast, Not Or; Worry Most About Being Ignored; The Rules of Direct Marketing Still Apply; Nothing Matters More Than the Brief; For Heaven's Sake, Try to Be a Good Client.
Includes index.
Online resource; title from digital title page (viewed on July 10, 2018).
Keywords: 2 -- 0; 6; Marketing.;Finance.;Marketing. -- Financial services industry.;Financial institutions;Bank marketing.;BUSINESS & ECONOMICS;Bank marketing.;Financial institutions;Financial services industry; 20; Electronic books. -- 2